Estimating of groundwater age and quality of Al-Shanafiya Area Southwest Iraq - Al-Shamma'a , Ayser. M.; M. Al-Mutawki, Kareem. G. (Iraqi Journal of Science, 2023)
The study area is located to the south of Iraq at Al-Shanafiya town, south west of Iraq. Groundwater is the main source for crops irrigation, household uses and livestock drinking. To determine the relative age of groundwater by measuring the tritium concentration in groundwater, four wells and four springs water samples were taken. Found that the mean tritium concentration in springs samples is 4.125 TU where in wells samples is 2 TU. Using Clark and Firtz (1997) classification found that the relative age is amix of sub modern and modern water. Through modern study was performed by Al-Paruany (2013) found that the tritium concentration in rainfall in Al-Diwaniyah Meteoric Station has reached the natural level (approximately 5TU). Through this , recent study can be applied by Mazor (2004) to determine the age of more accurate, found that the spring water effective age may be not more than 5 years. Eighteen representative groundwater samples were collected from wells and springs, were subjected to chemical analysis to measurement the major ions concentration. The water samples are alkaline in nature, they have high TDS and EC. Piper classification was applied and found that the groundwater samples are confined in the fields 2, 3 and 5 (Na-Cl, Ca-Mg-Cl and Ca-Cl water types). Chadha's diagram was applied for better understanding, water samples are confined in the fields 6, 4 and 7, nearly identical with Piper classification. The groundwater is unsuitable for human drinking, building and for all industries. But it is suitable for domestic uses and live stocks. The suitability of groundwater for irrigation, the samples (S1, S2, W1, W8, and W13) are fair water while the other samples were classified poor water.